Physical and sport education for life and soft skills development - Sara Aliberti; Generosa Manzo (Pensa MultiMedia, 2023)
Physical education (PE) can be a useful tool to promote life/soft skills. Schools highlight the importance to combine the construction of knowledge with an education that provides students the means to face the challenges of daily life. In Italy, although life/soft skills are recognized as important competencies for the individual, there is no kind of ministerial decree about them. The purpose of the essay was to present a brief review of studies concerning the effectiveness of programs implemented during PE hours on development of life/soft skills, in order to decline new thematic cores that take into consideration the emerging results. The method was the literature review. From the studies identified, PE was found to be a discipline that can promote the development of life skills. It would be useful to update the National Directions, which declines the goals for the development of PE competencies and learning objectives.